PENERAPAN MODIFIKASI BOLA PLASTIK UNTUK MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI PADA SISWA KELAS IV A SDN DUPAK V SURABAYA - SUPRIYONO, (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In sport and art lesson in SDN Dupak V Surabaya volley ball passing training have been performed but the result remain poor. In previous learning teacher used direct learning that have limitations: teacher dominated in learning, lack of feedback relationship, students were individualistic and had poor cooperation. It was shown by assessment performed to grade IV A SDN Dupak V Surabaya where 11 students got score of 70 or more or 27.50% where good. This research used plastic ball modification to improve student training result. Therefore training can be modified by lessening game structure hence playing basic strategy can be easily accepted by student. This research aimed to identify low passing training result improvement by using plastic ball modification for student at grade IV A SDN Dupak V Surabaya. Research performed by researcher was experiment research using action research approach in class room scope or called class acting research (PTK). Subject of research was all students of grade IV A SDN Dupak V Surabaya. It is caused by all problems were raised in this class. Number of students was 40 students with 19 male students and 21 female students. Keywords :  Class Act Research (PTK), Plastic Ball Modification, Volley Ball Low Passing